2015
DOI: 10.1007/s10534-015-9897-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological implications of mammalian ferritin-binding proteins interacting with circulating ferritin and a new aspect of ferritin- and zinc-binding proteins

Abstract: Serum ferritin levels are relatively low (<1 µg/ml) and serum ferritin generally disappears rapidly from the circulation (t 1/2 < 10 min). There are various mammalian ferritin-binding proteins (FBPs) in the blood. Ferritin is cleared by direct uptake by ferritin receptors and by indirect receptor-mediated uptake of FBP complexed with ferritin. Mammalian ferritin binds both heme and iron, and binding occurs through two mechanisms: direct binding with ferritin to H-kininogen and anti-ferritin autoantibody, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The present study suggests that IgG and fibrinogen interact with each other and/or bind zinc ions with different mechanisms. Zinc ions are taken up intracellularly by transporters but may also be indirectly taken up by receptors for zinc-binding proteins [22]. Further research is required to elucidate how important variables such as body condition, aging, species specificity and various zinc-binding proteins affect zinc availability.…”
Section: Resultsmentioning
confidence: 99%
“…The present study suggests that IgG and fibrinogen interact with each other and/or bind zinc ions with different mechanisms. Zinc ions are taken up intracellularly by transporters but may also be indirectly taken up by receptors for zinc-binding proteins [22]. Further research is required to elucidate how important variables such as body condition, aging, species specificity and various zinc-binding proteins affect zinc availability.…”
Section: Resultsmentioning
confidence: 99%
“…However, further study needs to clarify the effect of PPIX-binding IgG on the antibody-antigen reaction due to the different affinities of antibodies to their respective antigen. In humans, fibrinogen and albumin are also known as a PPIX and/or heme-binding protein in addition to IgG [16], and these proteins may play a protective role against oxidative stress caused by PPIX itself and/or iron as radical scavenger [15,16]. On the other hand, albumin shows stronger binding to PPIX than IgG [8].…”
Section: Resultsmentioning
confidence: 99%
“…First, stabilin-1 may have a role as a scavenger receptor for serum ferritin at the surface of macrophages and/or liver sinusoidal endothelial cells. There is general agreement that cells uptake ferritin through two routes: direct uptake by ferritin receptors and indirect uptake by ferritin-binding proteins 14 . It was shown that SCARA5, which belongs to scavenger receptor class A, mediates the uptake of ferritin iron in specific cell types in the developing kidney in mice 16 , and that SCARA5-transfected cells can bind or internalize human L-ferritin and H-ferritin 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, tissue of origin, secretory pathway, receptor interactions, clearance, and functions remain topics of active debate [11][12][13] . It has been hypothesized that ferritin clearance occurs through two different routes: direct uptake by specific ferritin receptors and indirect uptake by ferritin-binding proteins 14 . So far, studies have led to the identification of ferritin receptors such as TIM2, SCARA5, and TFR1 [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%